The effect of NLRP inflammasome on the regulation of AGEs‐induced inflammatory response in human periodontal ligament cells. (27th June 2019) - Yi, Xiaowei; Zhang, Lan; Lu, Wanlu; Tan, Xuelian; Yue, Junli; Wang, Puyu; Xu, Weizhe; Ye, Ling; Huang, Dingming
Abstract: Background and Objective: Diabetes influences the frequency and development of periodontitis. Inflammation of human periodontal ligament cells (HPDLCs) participates in this pathologic process. Hence, this study aims to explore whether advanced glycation end products (AGEs), by‐products of diabetes, could exaggerate inflammation induced by muramyl dipeptide (MDP) in HPDLCs, and whether nucleotide‐binding oligomerization domain‐like receptors (NLRs) signaling pathway was involved. Material and Methods: Human periodontal ligament cells were pre‐treated with 100 μg/mL AGEs for 24 hours and stimulated with 10 μg/mL MDP for 24 hours. IL‐6, IL‐1β, and RAGE were detected, and the activation of NF‐κB signaling pathway was observed. The expression of NLRs was evaluated with or without silencing RAGE or blocking NF‐κB pathway under AGEs stimulation. Statistical analyses were performed by using independent sample t test. Results: Advanced glycation end products induced significant increase of inflammatory cytokines in HPDLCs ( P < 0.05). Results of western blot (WB) showed that after 45 minutes stimulation of AGEs, p‐p65/p65 ratio peaked; AGEs promoted the expression of NLRP1, NLRP3, and apoptosis‐associated speck‐like protein containing a CARD (ASC). After silencing RAGE or blocking NF‐κB pathway, the up‐regulation of NLRs protein caused by AGEs was attenuated. Additionally, AGEs pre‐treatment could enhance the inflammatory response of MDP and the expression of NLRs, which were demonstrated by more expression of IL‐6, IL‐1β, NOD2, NLRP1, NLRP3, and ASC. Conclusion: Advanced glycation end products induced inflammatory response in HPDLCs via NLRP1‐inflammasome and NLRP3‐inflammasome activation in which NF‐κB signal pathway was involved. Besides, AGEs promoted the inflammatory response of MDP via NOD2, NLRP1‐inflammasome, and NLRP3‐inflammasome.